Electric ambulances: will the need for charging affect response times? - Nanne A. Dieleman; Caroline J. Jagtenberg (Health Care Management Science, 2026)
Abstract Ambulance providers currently rely on diesel vehicles for patient transport in their daily operations, but the first providers will likely transition to electric vehicles in the coming years. Prior to this transition, they would want to assess whether the non-negligible charging times impact response times. Our paper introduces this novel application and performs a study focused on range and charging infrastructure. We developed ELASPY, an open-source decision support system based on discrete-event simulation built in Python, to simulate the emergency response process, and used it to predict under which battery capacities and charger locations an electric ambulance fleet would achieve response times comparable to the equivalent diesel fleet. We also include a simulation-based optimization framework for charger allocation. We present a case study for the province of Utrecht, the Netherlands, from which derive managerial insights for ambulance providers. Our results did not reveal concerning signals for daily operations under the expected operating conditions. However, the sting is in the tail, and even ambulance providers with a low busyness will have to think about calamities such as prolonged power outages. We encourage decision makers to insert their own historical incident data into ELASPY and assess how transitioning from diesel to electric ambulance vehicles would affect response times in their region. The software is publicly available including documentation and set-up guidelines.